Isolated bilateral hypoglossal nerve paralysis following an atlanto-occipital dislocation: A case report - Mano, Tomoo; Tatsumi, Saori; Fujimura, Shigekazu; Hotta, Naoki; Kido, Akira (Frontiers in Neurology, 2022)
The present report highlights a case of successful treatment of an 11-year-old male patient who presented with an atlanto-occipital dislocation and multiple fractures of the forearm, pelvis, and lower leg because of a fall. The patient experienced dysarthria and paralysis of the tongue, which became completely immobile and could not be moved from side to side, impeding speech. The patient also experienced dysphagia due to the inability to propel food toward the pharynx and chewing attempts resulted in scattering of food residue throughout the oral cavity. The lack of tongue mobility led to saliva accumulation, forcing the patient to swallow frequently, which was possible as larynx movement was unaffected. The other cranial and motor sensory nerves appeared normal. Our diagnostic examinations confirmed the presence of isolated bilateral paralysis of the hypoglossal nerve secondary to traction at the base of the skull. The patient was still unable to protrude his tongue and tongue gradually atrophied two weeks after admission. Electromyography revealed denervation of the tongue and minimal active contraction of the single motor units. Immobilization therapy and rehabilitation therapy were initiated to improve tongue movement, but this was unsuccessful and one month after the accident, the patient's tongue was still atrophied. The patient was placed on a soft food diet and experienced no difficulty in swallowing either saliva or food three months after admission. Tongue mobility was deemed normal. Electromyography six months after the initial episode revealed normal motor unit potentials during contractions. We postulate that compression and stretching of the bilateral hypoglossal nerves against the greater horn of the hyoid bone was a probable cause of the hypoglossal palsy. The use of immobilization and rehabilitation therapy likely supported the recovery of functionality and resulted in a good prognosis.